Learning Anxiety of Undergraduate Students during COVID-19 Pandemic - Kittiphong Phanchamlong,; Kullasatree Manee,; Nuttapong Watwiset,; Prasart Nuangchalerm,; Veena Prachagool, (Journal of Educational Issues, 2024)
As we known the pandemic situation leads our social activity and learning practices changes, Online learning is the alternative choice for engaging students to classroom, but it is necessary may be students and teachers are unfamiliar with uncommon situation. The purpose of this research was to study learning anxiety of undergraduate science students during COVID-19 pandemic. The informants are 107 undergraduate science students enrolled course in the first semester, academic year 2021. The research instrument is developed as learning anxiety questionnaire which consisted aspect of time, instruction, and online communication. Descriptive statistics are employed for data analysis, data is interpreted by mean and standard deviation to explain level of learning anxiety. Finding showed that science students had leaning anxiety in aspect of time, instruction and online communication are at the high level. It indicated students are unfamiliar with virtual or online classroom, but they need to adapt themselves to learn and survive with this period of uncommon learning. This situation needs instructional practices through flexible learning and suitable effective ways for helping students achieve in their potential learning.